KOMPETENSI PROTOKOLER SEKRETARIAT DAERAH KABUPATEN BOLAANG MONGONDOW TIMUR - Risella Tombokan , Rivaldo; Bogar, Wilson; H. E. Sendouw, Recky (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study aims to analyze the competence of protocol officers in the Protocol and Communication Division of the Regional Secretariat of Bolaang Mongondow Timur Regency. The findings indicate that the protocol officers’ competencies are still inadequate, as evidenced by technical errors such as tardiness, lack of mastery in protocol regulations, and poor communication skills. Limited personnel and budget constraints exacerbate the situation, hindering the smooth execution of leaders’ agendas. To address these issues, continuous training to enhance technical and managerial competencies and a stricter selection process for protocol officer recruitment are essential. Additionally, increased budget allocation is necessary to expand personnel numbers and support operations. These measures are expected to improve the professionalism of protocol officers, ensure the seamless execution of leaders’ activities, and enhance the regional government’s image.